2022
DOI: 10.1007/s10639-022-11480-z
|View full text |Cite
|
Sign up to set email alerts
|

Can learning presence be the fourth community of inquiry presence? Examining the extended community of inquiry framework in blended learning using confirmatory factor analysis

Abstract: Researchers continue to extend the community of inquiry (COI) framework, highlighting its utility in online and blended learning environments for providing a successful learning experience. Recent studies have added the learning presence dimension to the classic COI framework which contains teaching, social, and cognitive presences, to represent online students’ traits of self-regulation. However, there is a need to examine whether this additional presence structurally represents relationships with other COI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The study results also demonstrated that social presence and learning presence significantly influence cognitive presence, illustrating that students who perceive high social interactions and apply motivational, behavioural, and developmental strategies during their learning process are likely to apply cognitive learning practices. Consistent with , Wertz (2014), Lin (2021), andElSayad (2023), who argued that students' social interactions and selfregulation are essential in online and blended learning environments to encourage their cognitive practices of inquiry, this study also emphasises their importance to encourage students' cognitive presence during the emergency blended learning environment. On the contrary, the findings showed an insignificant relationship between teaching presence and cognitive presence, which contradicts previous studies' findings Wertz, 2014;Zhang & Lin, 2021).…”
Section: The Structural Relationships Among the Extended Community Of...supporting
confidence: 75%
See 2 more Smart Citations
“…The study results also demonstrated that social presence and learning presence significantly influence cognitive presence, illustrating that students who perceive high social interactions and apply motivational, behavioural, and developmental strategies during their learning process are likely to apply cognitive learning practices. Consistent with , Wertz (2014), Lin (2021), andElSayad (2023), who argued that students' social interactions and selfregulation are essential in online and blended learning environments to encourage their cognitive practices of inquiry, this study also emphasises their importance to encourage students' cognitive presence during the emergency blended learning environment. On the contrary, the findings showed an insignificant relationship between teaching presence and cognitive presence, which contradicts previous studies' findings Wertz, 2014;Zhang & Lin, 2021).…”
Section: The Structural Relationships Among the Extended Community Of...supporting
confidence: 75%
“…Teaching presence is a key factor in the community of inquiry framework because it has a significant role in building a sense of community (Garrison et al, 2010;Tolu, 2013). During the online and blended learning processes, instructors' presence facilitates students' social interactions, promotes their motivations, behaviours, and intellectual development, and encourages their cognitive presence (ElSayad, 2023;Law et al, 2019;Zhang et al, 2010). Jansen et al (2020) and Zhang and Lin (2021) asserted that teaching presence, by providing structural teaching activities and immediate interventions during the online learning process, promotes students' self-regulation.…”
Section: Relationships Among the Community Of Inquiry's Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings provided evidence of a strong correlation between learning presence and cognitive presence of the classic COI, along with positive relationship significance between cognitive and social presence, implying that learning presence impacts social and cognitive presence. The findings suggest the extended COI framework's validity and reliability, including learning presence (ElSayad, 2022).…”
Section: Student Success In Online or Hybrid Courses Can Be Influence...mentioning
confidence: 78%
“…The classic COI framework model describes presence as a combination of teaching presence, social presence, and cognitive presence (Garrison et al, 2000). ElSayad (2022) conducted a study to explore learning presence, as a fourth presence of COI "to reflect online students' self-regulation process," and its correlation with the three presences of the classic COI to establish validity and reliability of the extended COI framework. The findings provided evidence of a strong correlation between learning presence and cognitive presence of the classic COI, along with positive relationship significance between cognitive and social presence, implying that learning presence impacts social and cognitive presence.…”
Section: Student Success In Online or Hybrid Courses Can Be Influence...mentioning
confidence: 99%